2022
DOI: 10.1002/casp.2635
|View full text |Cite
|
Sign up to set email alerts
|

Thinking too much: How young people experience rumination in the context of loneliness

Abstract: The recent rise in the prevalence of loneliness, particularly among young adults, coupled with its deleterious effects on wellbeing, makes understanding the issue of pressing concern. As most research on loneliness has focused on older adults, this study explored how 48 young adults aged 18-24 subjectively experienced loneliness through free association-based interviews. Participants were sampled from the four most deprived boroughs in London, as area deprivation has been associated with a higher prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Pittman and Reich (2016) showed that the image‐based use of social media is related to less loneliness, likely due to increased intimacy and social presence. However, it is noteworthy that any content, regardless of its form, can also incite unfavourable psychological mechanisms, such as comparing oneself negatively to others (Yang, 2016) or rumination related to others (Yun, Fardghassemi, & Joffe, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pittman and Reich (2016) showed that the image‐based use of social media is related to less loneliness, likely due to increased intimacy and social presence. However, it is noteworthy that any content, regardless of its form, can also incite unfavourable psychological mechanisms, such as comparing oneself negatively to others (Yang, 2016) or rumination related to others (Yun, Fardghassemi, & Joffe, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is noteworthy that any content, regardless of its form, can also incite unfavourable psychological mechanisms, such as comparing oneself negatively to others (Yang, 2016) or rumination related to others (Yun, Fardghassemi, & Joffe, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recent qualitative research also yielded evidence pointing to the existence of loneliness-related rumination. 26 Our new measure of automatic thoughts about loneliness is described below. We wrote items that comprise the Loneliness Automatic Thoughts Questionnaire with the expectation that we were tapping one dimension comprised of extreme and intense automatic thoughts about loneliness.…”
mentioning
confidence: 99%